Pengaruh Model Pembelajaran Visual Auditory Kinestetik dan Motivasi Belajar Terhadap Kompetensi Pengetahuan IPS Siswa Kelas IV SD Gugus Srikandi Denpasar Timur Tahun Pelajaran 2016/2017 - I Gusti Ngurah Made Anom Parbawa (Jurnal Ilmiah Sekolah Dasar, 2018)
This research is an experimental research with the research design used is a quasi-experimental design (nonequivalent control group design). Data were collected by IPS knowledge competency test and motivational learning questionnaire and analyzed using two-way ANAVA. The result of the analysis shows that there is a significant difference of IPS knowledge competence between students who are taught through VAK learning model with group of students which is learned through conventional learning, the result of research is based on data analysis with FA count = 7,25 and F table at significant level 5% with dk = 61 is 4.00, then H0 is rejected, (2) there is a significant difference of IPS knowledge competence between students who have high learning motivation with students who have low learning motivation, research results based on data analysis with FA count = 7.72 and F table at 5% significant level with dk = 61 is 4.00, then H0 is rejected, (3) there is interaction between learning model of VAK and learning motivation to IPS knowledge competence in fourth grader of SD Srikandi East Denpasar year 2016 / 2017Thus, it can be concluded that there is the influence of VAK learning model and learning motivation to IPS knowledge competence in fourth grade students of SD Srikandi Denpasar Timur school year 2016/2017.